Trichinella spiralis: genome database searches for the presence and immunolocalization of protein disulphide isomerase family members. Issue 1 (5th December 2014) - Freitas, C.P.; Clemente, I.; Mendes, T.; Novo, C.
Abstract: The formation of nurse cells in host muscle cells during Trichinella spiralis infection is a key step in the infective mechanism. Collagen trimerization is set up via disulphide bond formation, catalysed by protein disulphide isomerase (PDI). In T. spiralis, some PDI family members have been identified but no localization is described and no antibodies specific for T. spiralis PDIs are available. In this work, computational approaches were used to search for non-described PDIs in the T. spiralis genome database and to check the cross-reactivity of commercial anti-human antibodies with T. spiralis orthologues. In addition to a previously described PDI (PDIA2), endoplasmic reticulum protein (ERp57/PDIA3), ERp72/PDIA4, and the molecular chaperones calreticulin (CRT), calnexin (CNX) and immunoglobulin-binding protein/glucose-regulated protein (BIP/GRP78), we identified orthologues of the human thioredoxin-related-transmembrane proteins (TMX1, TMX2 and TMX3) in the genome protein database, as well as ERp44 (PDIA10) and endoplasmic reticulum disulphide reductase (ERdj5/PDIA19). Immunocytochemical staining of paraffin sections of muscle infected by T. spiralis enabled us to localize some orthologues of the human PDIs (PDIA3 and TMX1) and the chaperone GRP78. A theoretical three-dimensional model for T. spiralis PDIA3 was constructed. The localization and characteristics of the predicted linear B-cell epitopes and amino acid sequence of the immunogens used for commercial production of anti-human PDIA3 antibodies validated the use of these antibodies for the immunolocalization of T. spiralis PDIA3 orthologues. These results suggest that further study of the role of the PDIs and chaperones during nurse cell formation is desirable.